Supplementary Table S4 from Validation of the Clinical Use of GIScar, an Academic-developed Genomic Instability Score Predicting Sensitivity to Maintenance Olaparib for Ovarian Cancer - Raphaël Leman (17314506) (2025)
Panel of gene used for the GIScar calculation (n =127)